Adolescents’ use and perception of commercial video games with implied sexual content in Colombia [Utilização e percepção de adolescentes sobre videogames comerciais com conteúdo sexual implícito na Colômbia] (2017)
Objective: Characterize the use and perception of video games with implied sexual content by high school students in Medellin. Methods: Descriptive cross-sectional study with 1124 adolescents within eighth to eleventh grades of four public educational institutions. It was applied an structure questionnaire with socio-demographic, psychosocial, knowledge and risk factors question associated with sexual health and access, use and perception of video games. Results: Highlights the high consumption of video games, bigger in male adolescents, as the lack of educational video games in sexual health, lack of control regarding the time spend with and adult content. Adolescents felt that video games developed their: mental agility, analysis capacity, problem solving and decision making. The purpose of game use is focused on the goals and overcome their own recorde and friends’ records, where men are more competitive. The implied sexual content was identified through: the design of characters, costumes, language, scenarios and relationships between characters, with marked sex difference. Conclusion: The consumption of video games as new cultural products in this study was high, with marked difference by sex. It showed the implied sexual content leading to rethink the traditional forms of sexual education through interactive pedagogical and immersive proposals that simulate reality. © 2017, Nucleo de Estudos da Saude do Adolescente. All rights reserved.